Rational Strategy to Stabilize an Unstable High‐Efficiency Binary Nonfullerene Organic Solar Cells with a Third Component. Issue 20 (3rd April 2019) - Zhu, Youqin; Gadisa, Abay; Peng, Zhengxing; Ghasemi, Masoud; Ye, Long; Xu, Zheng; Zhao, Suling; Ade, Harald
Abstract: Long device lifetime is still a missing key requirement in the commercialization of nonfullerene acceptor (NFA) organic solar cell technology. Understanding thermodynamic factors driving morphology degradation or stabilization is correspondingly lacking. In this report, thermodynamics is combined with morphology to elucidate the instability of highly efficient PTB7‐Th:IEICO‐4F binary solar cells and to rationally use PC71 BM in ternary solar cells to reduce the loss in the power conversion efficiency from ≈35% to <10% after storage for 90 days and at the same time improve performance. The hypomiscibility observed for IEICO‐4F in PTB7‐Th (below the percolation threshold) leads to overpurification of the mixed domains. By contrast, the hypermiscibility of PC71 BM in PTB7‐Th of 48 vol% is well above the percolation threshold. At the same time, PC71 BM is partly miscible in IEICO‐4F suppressing crystallization of IEICO‐4F. This work systematically illustrates the origin of the intrinsic degradation of PTB7‐Th:IEICO‐4F binary solar cells, demonstrates the structure–function relations among thermodynamics, morphology, and photovoltaic performance, and finally carries out a rational strategy to suppress the degradation: the third component needs to have a miscibility in the donor polymer at or above the percolation threshold, yet also needs to be partly miscible with the crystallizable acceptor. Abstract : The high‐performance PTB7‐Th:IEICO‐4F system exhibits an inherent performance degradation resulting from demixing and crystallization failure. Incorporation of a third component which has a miscibility in the donor polymer at or above the percolation threshold, yet is also partly miscible with the crystallizable acceptor can remedy the performance degradation.